Reguła mistrza o wyborze i nauczaniu opata - Czyżewski, Bogdan (Vox Patrum, 2018)
The monasteries which were raised in the Church in first centuries demanded rules stating life of their members. The initatior and founder of these monasteries was saint Pashomius. It’s noteworthy to remind anonymous work which were made in nine century called The Regula Magistri. This extensive ancient opus containing collection of monastic rules written by author of unknown name, was created in about fifth century south of Rome. Nowadays, we assume that The Regula Magistri became a model for the rule of Saint Benedict. The Rule of the Master was written for the monastery where the leading role was up to Abbot. He was the one who was preaching, teaching and he, indeed, was a master for his disciples. Several chapter of this monumetal work is dedicated to the rules and procedures of choosing the abbot. It also contains list of the most important tasks which belonged to his office – these are the subject of this study. What’s interesting is that, the new abbot was being elected by his predecessor when he sensed that he is going to die shortly or serious ill makes him incapable of continuing his tasks. Abbot was looking after his brothers and encouraged them to acquire virtues. This kind of challenge could seem useful, because it was the motivating factor to, fulfill God’s will with dignity and humble, and also to life by the abbey’s rules. On the other hand, it could also had been dramatic, because the ascetic way of life sometimes was understood only in human succes category. The candidate was introduced on his duty by local bishop in special liturgical rite. There were also rules dedicated to possibly removal of the abbot, who – when his predecessor still lived – seemed to be unhumble and improper man for this office. The Rule also contains special instruction for the situation, when abbot dies in sudden death and had not decided who would have been his successor. The author of the Master’s Rule also draws attention to the manner of teaching conducted by the Abbot. The most important was the testimony of life, fidelity to the binding rules, exercising in virtues and avoiding sins. The Rule of the Master teach the Abbot, that he should be humble, treat the brothers equally, be responsible for the others and for himself, and ask as all brother for the opiniong in issues relating to the monastery.